Penggunaan Prebiotik Oligosakarida Ekstrak Tepung Buah Rumbia (Metroxylon sago Rottb.) dalam Ransum terhadap Performan Ayam Pedaging - Muhammad Daud; Wiranda G Piliang; Komang G Wiryawan; Agus Setiyono (Agricultural Faculty, 2009)
Effect of prebiotic oligosaccharide extract rumbia fruit (Metroxylon sago Rottb.) in the ration on broiler performanceABSTRACT. Prebiotic oligosaccharides are thought to provide beneficial effects in the gastrointestinal tract of humans and animals by stimulating growth of selected members of the intestinal microflora. Prebiotic oligosaccharides are defined as nondigestible food ingredients that provide beneficial effects to the host by stimulating the growth of selected microbial members of the gastrointestinal tract. Among the colonic bacteria capable of metabolizing prebiotic oligosaccharides and whose growth is stimulated are species of Lactobacillus and Bifidobacterium. Prebiotic oligosaccharides can be produced in transgli-cosylation reactions catalyzed by glycosidases. Glycosidases from different biological sources have specific ability to catalyze the formation of oligosaccharides with particular chain lengths (usually DP 7) and predominant glycosidic linkages. Oligosaccharide used this research was purified rumbia fruit extract as prebiotic for feed additive in the ration on broiler. The objectives of this research were to study the performance of broiler given of prebiotic oligosaccharide extract rumbia fruit (metroxylon sago Rottb.) in the ration. Two hundred day-old chicks of broiler were divided into three dietary treatments and four replications. Ration used was consisted of: R1 = basal ration (control), R2 = basal ration + 0,4% oligosaccharide extract rumbia fruit, and R3 = basal ration + 0,4% frukto-oligosaccharide (FOS). The variables observed were: feed consumption, body weight, feed conversion ratio, mortality, and production index. The result showed that the performances of the broiler supplemented prebiotic oligosaccharide extract rumbia fruit (R2) was significantly (P 0.05) differences between of feed consumption, body weight, and mortality. It is concluded that of prebiotic oligosaccharide extract rumbia fruit were able to decrease the mortality and feed consumption at six week of age.